Relationship between general self-efficacy, social support and resilience of physically restrained patients in ICU (ICU身体约束患者自我效能、社会支持和心理弹性的相关性研究) - LIN Ruyu (林如玉); ZHAO Huiling (赵慧玲); BIE Yuanyuan (别园园); CHEN Qiaoling (陈巧玲) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the role of general self-efficacy in social support and resilience of physically restrained patients in ICU. Methods The purposive sampling strategy was adopted, and 221 physically restrained patients in ICU were investigated by using Connor-Davidson Resilience Scale(CD-RISC), General Self-Efficacy Scale(GSES)and Social Support Rate Scale(SSRS). Results The averaged score of CD-RISC was (51. 68±9. 03), the total score of SSRS was (36. 47±7. 79), and total score of GSES was(23. 63±4. 80). Pearson correlation analysis showed that the social support level was positively correlated to the resilience of patients (r=0. 637, P＜0. 001), and self-efficacy was negatively correlated to the resilience of patients(r=0. 616, P＜0. 001). Linear regression indicated the subjective support and self-efficacy as two main factors influencing the resilience(P＜0. 001). The self-efficacy played a partial mediating role (38. 40%) social support and resilience. Conclusion Findings showed a poor resilience of physically restrained patients in ICU, and support and self-efficacy were two main factors influencing the resilience. It is required to carry out diversified psychological interventions to improve the resilience of physically restrained patients in ICU. (目的 探讨ICU身体约束患者自我效能在社会支持和心理弹性中的作用。方法 采用目的抽样的方法, 应用心理弹性量表、一般自我效能感量表以及社会支持评定量表, 对2021年9月-2022年4月的221例ICU身体约束患者进行问卷调查。结果 ICU身体约束患者的心理弹性得分(51. 68±9. 03)分, 社会支持总分为(36. 47±7. 79)分, 自我效能总分为(23. 63±4. 80)分。Pearson相关性分析显示社会支持与心理弹性呈正相关(r=0. 637, P＜0. 001), 自我效能与心理弹性呈正相关(r=0. 616, P＜0. 001); 线性回归显示主观支持、自我效能感是心理弹性最主要影响因素(P＜0. 001); 中介效应分析显示: 自我效能在社会支持和心理弹性中起部分中介作用, 相对效应为38. 40%。结论 ICU身体约束患者的心理弹性差, 自我效能、社会支持是心理弹性的重要影响因素, 应通过多元化的心理干预策略以提升该群体心理弹性。)